Comparison of Verdicts in Handling Election Violations Through Coordination of Gakkumdu Center North Lampung Regency - Baharudin , Baharudin; Sari, Putri Intan (Amsir Law Journal, 2022)
Sovereignty is in the hands of the people as mandated in Article 1 Paragraph 2 of the 1945 Constitution of Republic Indonesia. The meaning of “sovereignty is in the hands of the people” in this case is that the people have sovereignty, responsibilities, rights and obligations to democratically elect a leader who will form a government to manage and serve all levels of society, as well as elect representatives of the people to oversee the running of the government. The research method used was normative and empirical juridical, using secondary and primary data, obtained from literature studies and field studies, and data analysis with qualitative juridical analysis. The suggestion is that the Gakkumdu Center at North Lampung Regency should provide concrete and important implementation rules to ensure legal certainty and justice.